Capital Efficiency Based on Payment Capability (CEPac) as a Mediator Between Asset Structure, Sales Growth, and Firm Value: Evidence from Indonesian Manufacturing Firms - Faisal Riza Rahman; Maduretno Widowati; Sugeng Wahyudi (Universitas Negeri Semarang, 2026)
This study introduces and empirically validates CEPac as a mediating construct linking asset structure and sales growth to firm value. Grounded in Trade-Off Theory, Resource-Based View, and Signaling Theory, CEPac integrates the inverse of the Weighted Average Cost of Capital (1/WACC) and Times Interest Earned (TIE) to capture financing efficiency and debt-servicing capacity. Using panel data from 75 manufacturing firms listed on the Indonesia Stock Exchange (2019–2023), seven hypotheses were tested through fixed-effects regression and Sobel mediation analysis in STATA. The results show that asset structure and sales growth significantly increase firm value, both directly and through CEPac (p<0.01), with mediation effects accounting for 18%–32% of the total influence. The model demonstrates strong explanatory power. Overall, the findings provide actionable insights for managers seeking to optimize capital allocation and operational growth, and position CEPac as a reliable financial assessment tool for capital-intensive industries.